Utility of Preoperative Laboratory Testing for Ambulatory Endoscopic Sinonasal Surgery in Low-Risk Patients. Issue 3 (May 2023) - Patel, Rushi; Shah, Sejal; Vedula, Sudeepti; Omiunu, Ariel; Patel, Prayag; Eloy, Jean Anderson; Baredes, Soly; Fang, Christina H.
Background: Preoperative laboratory tests (PLTs) are often obtained prior to outpatient surgical procedures. The objective of this study is to examine the current practice of routine PLT in low-risk patients undergoing ambulatory endoscopic sinonasal surgery (ESS) and to assess whether such testing impacts surgical outcomes. Methods: Patients undergoing ambulatory ESS were identified from the 2011 to 2018 NSQIP database. Low-risk patients were defined as American Society of Anesthesiologist class 1 or 2. PLTs were grouped into hematologic, chemistry, coagulation, and liver function tests. Chi-square analyses and independent samples t -tests were conducted to compare categoric and continuous variables, respectively. Results: A total of 664 cases met the inclusion criteria, of which 419 (62.1%) underwent at least one PLT. Of these, the most frequent PLT obtained was a complete blood cell count (92.4%). Major complications occurred in 1.5% of patients. There were no statistically significant differences in overall postoperative complications between those with and without PLT ( P = .264). Specifically, no significant difference was seen in the incidence of postoperative bleeding ( P = .184), urinary tract infection ( P = .444), pulmonary embolism ( P = .444), or wound infection ( P = .701). On multivariable analyses, PLT status was not significantly associated with any complication ( P = .097) or unplanned readmission ( P = .898). Conclusions: Our analysis did not reveal an association between the use of PLT and postoperative morbidity or unplanned readmission in low-risk patients undergoing outpatient ESS.